Perjanjian Gadai Sawah Pada Masyarakat Tigo Luhah Kemantan Kabupaten Kerinci - Taufiq, Muhammad; Idris, Isran; Naili Hidayah, Lili (Universitas Jambi, Fakultas Hukum, 2024)
The purpose of writing this article is to find out and analyze the rice pawn agreement made by the Tigo Luhah Kemantan community of Kerinci Regency according to customary law if it is related to Law Number 56 Prp of 1960 concerning Determination of Agricultural Land Area and to find out about the factors that cause difficulties in redemption in agreement to pawn rice fields in the Tigo Luhah community, Kemantan, Kerinci Regency. The research is empirically juridical in nature, namely to examine the effectiveness of the enforcement of a legal norm. The results of the research show that 1) the implementation of pawning rice fields which is carried out according to customary law shows that there are elements of extortion so that it is not in accordance with what is expected and regulated in the law, because the land can be used by the recipient of the pawn, the risk of changes in the value of the currency is completely borne by the giver. pledge, and the pledge lasts indefinitely; 2) there are several factors behind why customary rice pawn agreements are difficult for the pawnbroker to redeem, namely from an economically disadvantaged perspective, changes in the currency value required during redemption, and the public's lack of knowledge of the laws and regulations related to the law. pawn the rice fields.